2013
DOI: 10.1016/j.febslet.2013.07.055
|View full text |Cite
|
Sign up to set email alerts
|

Concerted action of activation‐induced cytidine deaminase and uracil‐DNA glycosylase reduces covalently closed circular DNA of duck hepatitis B virus

Abstract: Edited by Hans-Dieter KlenkKeywords: AID APOBEC Base excision repair Hepatitis B virus cccDNA a b s t r a c t Covalently closed circular DNA (cccDNA) forms a template for the replication of hepatitis B virus (HBV) and duck HBV (DHBV). Recent studies suggest that activation-induced cytidine deaminase (AID) functions in innate immunity, although its molecular mechanism of action remains unclear, particularly regarding HBV restriction. Here we demonstrated that overexpression of chicken AID caused hypermutation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
3
13
0
Order By: Relevance
“…In contrast, AID expression is not observed in normal hepatocytes. Similarly, overexpression of chicken AID causes hypermutation in association with reduction of duck HBV covalently closed circular DNA levels [99]. Consistent with the immunohistochemistry on human clinical tissue specimens, AID expression is upregulated in response to stimulation by proinflammatory cytokines, such as TNF-α or IL-1β, or expression of HCV core protein in cultured human hepatocytes [95,96].…”
Section: Hepatocytessupporting
confidence: 64%
“…In contrast, AID expression is not observed in normal hepatocytes. Similarly, overexpression of chicken AID causes hypermutation in association with reduction of duck HBV covalently closed circular DNA levels [99]. Consistent with the immunohistochemistry on human clinical tissue specimens, AID expression is upregulated in response to stimulation by proinflammatory cytokines, such as TNF-α or IL-1β, or expression of HCV core protein in cultured human hepatocytes [95,96].…”
Section: Hepatocytessupporting
confidence: 64%
“…3). It has been recently reported that chicken AID reduced cccDNA of duck HBV possibly through targeting cccDNA as well as nucleocapsid-associated HBV DNA (75). This study is likely to support the idea that AID may target cccDNA formed after HBV entry into hepatocytes, and also associates with nucleocapsid-associated HBV DNA during HBV replication, although it is not clear whether the innate immune machinery against HBV/duck HBV is conserved in human and chicken cells.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-␤ could also induce cccDNA deamination and degradation in hepatocytes via activation-induced cytidine deaminase (AID) (176), which has been described to mediate degradation of duck HBV (DHBV) cccDNA (177). The effect elicited by TGF-␤ was abrogated when AID or the activity of uracil N-glycosylase (UNG) was blocked, indicating that AID-mediated deamination and the excision of uracil by UNG act in concert to degrade HBV cccDNA (176).…”
Section: Immune Clearance Of Hbv Cccdnamentioning
confidence: 99%